The Quarterly Journal of Economics Volume 131 February 2016 Issue 1 - Front Cover (Quarterly Journal of Economics, 2016)
Journal Article The Quarterly Journal of Economics Volume 131 February 2016 Issue 1 - Front Cover Get access The Quarterly Journal of Economics, Volume 131, Issue 1, February 2016, Page i1, https://doi.org/10.1093/qje/qjv043 Published: 22 February 2016